Brain Fitness Exercises And Meditation Practice on Cognitive Skills Among School Students: An Experimental Study - Srinath CV; Cherappurath , Nafih (International Journal of Psychosocial Rehabilitation, 2020)
The present study was to analyse the effect of brain fitness exercise and meditation practice on cognitive skills among tribal school students in Kerala, India. To achieve this purpose, a total of seventy-five (n = 75) students (age ranged between 10 to 15 years old) were randomly selected from Kerala, India and divided into three groups twenty-five (n = 25) namely, Meditation practice group (MTG), Brain fitness group (BFG) and control group (CG). The training period was twelve weeks and six days a week. The investigator used the NIMHANCE cognitive skill assessment test for the assessment of various cognitive skills. The experimental groups, meditation practice, and brain fitness exercise groups showed statistically higher increases in cognitive skills (p<0.05); The brain fitness exercise group showed a higher mean difference than the meditation group and control group didn’t show any significant differences. In conclusion, 12 weeks of Meditation practice and Brain fitness exercise programmes in tribal school students results in significant improvements in cognitive skills.